Strategi Internasionalisasi Perguruan Tinggi: Studi Multikasus pada Universitas Islam Malang dan Universitas Muhammadiyah Malang - Abdul Muis Pawero (Institut Agama Islam Negeri (IAIN) Manado, 2017)
Internationalization of private colleges at UN/SMA and UMM with the discussion ocusing on (1) internationalization strategies, (2) factors supporting internationali zation, and (3) challenges of internationalization at UN/SMA and UMM. This study used a qualitative approach with multiplecase study design. Data were collected using deep interviews, observations and documentation. The results show that inter nationalization strategies at both universities consist of two dimensions, namely inter nal strategies and external strategies. Internal strategies at both universities are insti tutionnal responses in the form of internal college-comprehensive policies that are significant from an organizational prespective. External strategies in the two unive rsities are actions of internationalization in a well refined plan. These actions come after both universities formulate the vision, mission and/or their strategic plans of internationalization.